DNA context and promoter activity affect gene expression inlentiviral vectors - Mao, G.; Marotta, F.; Yu, J.; Zhou, et al., L. (Acta Biomedica Atenei Parmensis, 2008)
Several varieties of lentiviral delivery systems have been used to generate stable cell lines and transgenic animals. Some enhancing elements have been identified to promote stable transgene expression.  In this study, we describe that the promoter activity is affected by the lentiviral genomic context.  We have examined the promoter activities using green fluorescence protein (GFP) as a reporter in different cell lines to demonstrate that the cytomegalovirus (CMV) promoter may not always be the best choice to overexpress transgenes in all cell types. Our data showed that the polypeptide chain elongation factor 1 alpha (EF1α) promoter is relatively active in all three model cell lines (293T, HOS, and Hela) while the CMV promoter is less effective in Hela cells.